Adequacy of the Global Financial Safety Net : Proposal for a New Policy Coordination Instrument. (Policy Papers; Policy Paper ;, 2017)
The global financial safety net (GFSN) has become larger and more decentralized, creating a need for greater coordination. The expanded GFSN has created multiple sources of official financing for countries in need of support to address balance of payments shocks. Enhanced coordination among these layers would facilitate a more efficient use of global resources and provide better incentives for implementing sound policies. A new non-financing Policy Coordination Instrument (PCI) would address gaps in the GFSN and the Fund's toolkit. The new Policy Coordination Instrument is designed for countries that are seeking to unlock financing from multiple sources and/or to demonstrate a commitment to a reform agenda. It would enable a closer policy dialogue between the Fund and countries, more regular monitoring of economic developments and policies, as well as Board endorsement of those policies. It would be available for all member countries. The key design features draw on Fund financing arrangements and the Policy Support Instrument (PSI), with some important differences. These include no qualification criteria, a review-based approach for monitoring of conditionality, and a more flexible review schedule. The PCI is part of a broader set of Fund policy proposals to improve coordination with RFAs, enhance liquidity provision for members, and ensure the cohesion of the Fund's toolkit. The IMFC and the G20 called for further work to strengthen the GFSN and to improve cooperation between the Fund and regional financing arrangements (RFAs). In response, the Fund has produced a diagnostic of the GFSN and the Fund's toolkit and identified important gaps. Introduction of the PCI, when considered together with the other proposals, will help to move towards a GFSN with improved coverage, more reliable support, and better coordination between the various layers.